MicroRNA expression in BRAF-mutated and wild-type metastatic melanoma and its correlation with response duration to BRAF inhibitors. (August 2015) - Pinto, Rosamaria; Strippoli, Sabino; De Summa, Simona; Albano, Anna; Azzariti, Amalia; Guida, Gabriella; Popescu, Ondina; Lorusso, Vito; Guida, Michele; Tommasi, Stefania
<x xml:space="preserve">Abstract</x> Objective: Currently, the treatment of BRAF V600-mutated metastatic melanoma with BRAF inhibitors gives a response rate of ∼ 50% with a progression-free survival of ∼ 6 – 7 months. In order to identify predictive biomarkers capable of stratifying BRAF-mutated patients at high risk of shorter response duration to anti-BRAF therapy, the authors analyzed the expression of 15 microRNAs (miRNAs) targeting crucial genes involved in melanoma biology and drug response. Research design and methods: A total of 15 miRNAs and target gene expression were investigated in 43 patients (30 BRAF-mutated, and 13 BRAF wild-type). Moreover, 20 BRAF-mutated patients treated with vemurafenib were analyzed for miRNA expression in respect to time-to-progression. Results: All miRNAs except miR-192 showed low expression in BRAF-mutated as compared with BRAF wild-type patients. In particular, miR-101, miR-221, miR-21, miR-338-3p and miR-191 resulted in significant downregulation in BRAF-mutated patients. Moreover, high expression of miR-192 and miR-193b* and low expression of miR-132 resulted in significant association with shorter progression. Conclusion: Three miRNAs were significantly associated with clinical outcome in metastatic melanoma patients. An increased understanding of the molecular assessment of BRAF-mutated melanomas could allow development of specific molecular tests able to predict response duration.